Low levels of text comprehension in students of multi-grade educational institution Nº 22343 of Longar - San Juan Bautista district - Ica, 2017 - Figueroa Cordero, Fabiola Magaly (2023)
The objective of this was to apply strategies to address the low levels of text comprehension in students of the Multigrade Educational Institution No. 22343 of Longar-District of San Juan Bautista-Ica, 2017. From the diagnosis made using the tree of problems, the needs of the children who studied in that educational institution were detected, these requirements were met with the following activities: Workshops for teachers in the Knowledge of the Textual Communicative Approach; Talks on the proper use of teaching materials in learning sessions; Sensitization of the actions of accompaniment and managerial advice to teachers in the area of communication, then, having executed the actions referred to with teachers, they applied their learning with students having achieved substantial changes.